Study of the effect of wind angles on the aerodynamic characteristics of high-speed trains subjected to a translating simulated tornado - Li, Mu; Gan, Jiankun; Zhang, Yuanzhao; Wu, Yecheng; Chai, Bo (Frontiers in Physics, 2024)
The probability of high-speed trains being hit by tornadoes is increasing. Therefore, this paper studies the effect of wind angles on the aerodynamic characteristics of a high-speed train subjected to a translating simulated tornado. A small six-dimensional force/torque sensor was used to measure the aerodynamic force and moment of a high-speed train model at a reduced scale of 1:150. The models, consisting of high-speed train heads and cars with different aerodynamic shapes, displayed non-stationary characteristics in their respective aerodynamic force and moment coefficient time histories. The variation trends of the ensemble time-varying mean of the pitching moment coefficient of a high-speed train car and head, for wind angles smaller than 60° and 45°, respectively, are different from those for other wind angles. The lift force coefficient ensemble time-varying mean of the high-speed train head is asymmetrical along the longitudinal axis when the wind angle is smaller than 60°, which is different from that of the high-speed train car. The maximum values of the ensemble time-varying mean of the force and moment coefficient of the high-speed train are almost equal under different movement directions of the tornado simulator at each wind angle, which is also true for the minimum value of the force and moment coefficient of the high-speed train. The ensemble time-varying variance of the force and moment coefficient of the high-speed train model in the region of −200 mm–200 mm is greater than that in other regions. This study can contribute to a more comprehensive and accurate understanding of the interaction between tornadoes and high-speed trains.